Pengaruh Daya Tarik Wisata dan Lokasi Terhadap Keputusan Berkunjung Wisatawan di Objek Candi Jiwa Batujaya Pada Masa Pandemi Covid - 19 - Mahpudin Mahpudin; Asep Maulana (Peneliti.net, 2022)
This study aims to determine the effect of tourist attraction and location on the decision of tourists to visit the Jiwa Batujaya Temple during the Covid-19 Pandemic. The approach used by the researcher is a descriptive and verification approach. Descriptive method is one that is used to determine the value of the independent factor, whether there is a possibility of the variable. The results of the study show that there is a correlation between tourist attraction and location with a correlation coefficient value of 0.450 and has a fairly strong criterion relationship level because the value is positive. There is a partial influence of tourist attraction and location on visiting decisions